Minimalistic Reconstruction Of Fingertip Injuries Using Artificial Dermal Substitutes: Analysis Of Early Clinical Outcomes - Chand, Prayash; Chand, Prapti; Magar, Roshani Thapa (Journal of Society of Surgeons of Nepal, 2024)
Background: Fingertip injuries, common yet complex, pose significant challenges in resource-limited settings where advanced surgical interventions are scarce. This study evaluates the use of artificial dermal substitutes for minimalistic reconstruction of fingertip injury. We have used Novosorb® Biodegradable Temporizing Matrix (BTM) combined with chlorhexidine-impregnated paraffin gauze for single-stage fingertip reconstruction in Nepal, emphasizing functional, sensory, and cosmetic outcomes. Methods: A retrospective single-centre study included 9 patients (13 digits) with fingertip injuries (Allen’s I–IV) treated between January 2022 and December 2024. Under digital nerve block, wounds were debrided, and BTM was applied, followed by daily home dressings. Outcomes included healing time, fingerprint regeneration (0–3 scale), sensory recovery (0–5 scale), pain (VAS 0–5), patient satisfaction (1–5 scale), and complications. Results: Mean healing time was 76 ± 12.51 days, correlating with injury severity (Allen’s I: 70 days; IV: 95 ± 4.24 days). Fingerprint regeneration was robust (mean score: 2.69 ± 0.48), with near-complete recovery in Allen’s I–II injuries. Patient satisfaction was high (overall: 4.31 ± 0.63; cosmetic: 4.08 ± 0.76), and sensory impairment (1.23 ± 0.43) and pain (1.30 ± 0.48) were minimal. Complications included hook nail (30.8%) and nail splitting (15.4%), primarily in Allen’s III–IV injuries. Conclusion: Artificial dermal substitutes like Novosorb® BTM offers a practical, minimally invasive solution for fingertip injuries in resource-constrained settings, preserving finger length, sensation, and function while avoiding donor-site morbidity. High patient satisfaction and functional outcomes underscore its viability as a first-line treatment specially for patient’s preferring single stage surgery. Larger prospective studies are warranted to validate long-term efficacy and refine protocols for complex cases.